Dualisme Lembaga Pendidikan di Indonesia: doi 10.58569/jies.v1i2.582 - Suryoto; Hitami , Munzir; Yusrianto , Edy (Pascasarjana Universitas Islam Jakarta, 2023)
The terms dualism and dichotomy have the same meaning, namely the separation between general education and religious education. Dichotomy always gives rise to different views on one side and equality on the other. The dichotomous view essentially ignores the essence or value of the spirit of education. Differentiating and equating are more interpreted at the surface level so that it clearly damages the spirit value of Islamic education. Dualism and dichotomy are not only at the level of segregation, but have entered the area of separation which in practice separates general subjects from religious subjects, public schools and madrasas which are managed separately. The climax was when the New Order government issued a Joint Decree (SKB) on March 24, 1975 which confirmed the separation to date. The impact was detrimental and the meaning of Islam became narrower because the compartmentalization of knowledge ultimately subordinated and neglected Islamic education. As an alternative solution, efforts to integrate knowledge and repositioning must be followed, namely the perspective of Islamic sciences in their true position.